STATISTICAL ANALYSIS OF WIND SPEED DISTRIBUTION WITH SINOP-TURKEY APPLICATION - Balpetek, N.; Akpinar, E. Kayak (Yildiz Technical Univ, 2019)
In this study, the wind energy potential of the Sinop region was analyzed statistically by using the Turkish State Meteorological Station's hourly wind speed data between the years of 2005-2014. The two- parameter Weibull and one-parameter Rayleigh probability distribution functions were used to determine the wind energy potential of the region. The probability distribution functions were derived from the cumulative function and used to calculate the mean wind speed and the variance of the actual data. The best way of representing the performance of the Weibull and Rayleigh distributions is to use the statistical parameters such as the correlation coefficient (R-2), chi-square (chi(2)) and the root mean square error analysis (RMSE). The results of the study showed that Sinop has a mean wind speed of 3.36 m/s with a maximum value of 4.28 m/s in February of 2011, and a minimum value of 2.41 m/s in March of 2013, while the corresponding mean wind power density is approximately 33.31 W/m(2) for the whole year. In general, it was determined the wind speed is higher during some winter and spring months, notably February and March, and is lower during the autumn months. The Weibull distribution function was found to be more appropriate than the Rayleigh distribution function.
Keywords: Wind Energy; Statistical Analysis of Wind Energy Potential; Weibull Distribution; Rayleigh Distribution; Sinop-Turkey